The comparative estimation of cryopreserved embryonic nervous cells and bone marrow stromal cells transplantation results in area of experimental epileptic center - Tsymbalyuk, V. I.; Kochin, O. V. (Ukrainian Neurosurgical Journal, 2005)
The comparative estimation of experimental epilepsy surgical treatment results in experiment with application of cryopreserved embryonic nervous cells and bone marrow stromal cells, inducted in neuroblasts, was carried out. It is established, that the cryopreserved embryonic nervous cells and bone marrow stromal cells, inducted in neuroblasts, transplanted in area of epileptic center not only keep their viability, but also were capable to differentiate in neurons. The similar positive dynamic of biogenic amines maintenance in a brain stem was marked in the groups of animals, in which the transplantation of cryopreserved embryonic nervous cells and bone marrow stromal cells, inducted in neuroblasts, have been executed.